Neuropharmacology of the Interoceptive Stimulus Properties of Nicotine - Wooters, Thomas E. (2009)
Preclinical drug discrimination techniques play a significant role in advancing our knowledge of the receptor mechanisms underlying the interoceptive effects of nicotine. Early reports confirmed that nicotinic acetylcholine receptors (nAChRs) are critical for transduction of the nicotine cue. In recent years, advances in molecular biology and the discovery of novel ligands with greater selectively for specific nAChR subtypes have furthered our understanding of these mechanisms. There is now evidence regarding the specific nAChR subtypes involved in nicotine discrimination; in addition, there is also evidence suggesting that other systems (i.e., adenosine, cannabinoid, dopamine, glutamate and serotonin) may play a modulatory role. The neuroanatomical structures mediating the nicotine cue have also begun to be elucidated. However, much remains to be learned about the predictive validity of the drug discrimination procedure, particularly with regard to the relation between interoceptive and reinforcing effects and individual differences in vulnerability to tobacco dependence. Recent data also suggests that the mechanisms involved in the conditional and discriminative stimulus properties of nicotine may be dissociable. Avenues for future research should include assessing the mechanisms of the subjective effects of nicotine withdrawal, factors contributing to individual differences in sensitivity to the nicotine cue, and the role of behavioral factors involved in drug cross-substitution.